Formation of a scientific approach to functioning as a process of development of innovation-oriented enterprises - Boiarynova, Kateryna (Technology audit and production reserves, 2017)
The object of research is considering the functioning of the development process of innovation-oriented enterprises in changing, turbulent economic conditions. The lack of available scientific approaches to the implementation of operational measures to develop innovative enterprises in the process of functioning has made it necessary to consider the functioning not as a process of life activity, but as a process of their operational development in the conditions of economic instability. The theoretical bases of functioning of innovation-oriented enterprises as a development process are scientifically grounded. It is revealed that in its implementation it is necessary to lay the scientific and methodological foundations of innovation-oriented development. The functioning of an innovation-oriented enterprise is defined as a process of operative, systematic implementation of functions aimed at changing the economic state of an enterprise in order to achieve the target development targets. It is justified to operate with the development of innovative enterprises and key concepts. The formed scientific approach allows to develop the organizational and economic bases for operating development in the process of functioning on the basis of fulfilling their economic functions as economic entities and in the system of economic relations.